Consequences of Economic Deconcentration in Italy and Rome: Unplanned Processes in a Highly Regulated Country. (25th June 2012) - Montanari, Armando; Staniscia, Barbara
Abstract : This paper analyses the relationship between deconcentration processes, planning policies, and governance in the metropolitan area of Rome, Italy, from 1991 to 2001. It points out that Rome does not have an explicit policy either in favor of or against deconcentration and that the public authorities are not in fact aware of the problem. Deconcentration is mainly driven by market forces and business location decisions. These decisions are strongly influenced by material factors such as accessibility, land availability, and real estate prices, as well as immaterial factors such as the natural, cultural, and social environment. Public players can take action to influence these factors. Even though Italy has a very strictly regulated planning system, there has traditionally been a high degree of freedom in actual behaviors.